Moral Convictions and Threats to Science. Issue 1 (March 2022) - Bayes, Robin
When science is marshaled to support one side or another in policy debates, people can react to that information differently depending on whether it supports their own position. They tend to find fault in unfavorable information and accept favorable information less critically. This may especially be the case when individuals' positions are held with moral conviction—that is, when their position is not only their preferred position, but when it is the position that they feel to be morally correct. I examine three areas in which allowing moral convictions to influence reactions to scientific information may actually threaten the social benefits of science: promoting science misperceptions, eroding the credibility of scientists as sources of information, and eroding evaluations of science as a process. I argue that dealing with the influence of moral conviction over scientific interpretation will require acknowledgement that the social benefits of science are not self-evident and that they depend on public buy-in.